Ischaemic concentrations of lactate increase TREK1 channel activity by interacting with a single histidine residue in the carboxy terminal domain. (17th November 2015) - Ghatak, Swagata; Banerjee, Aditi; Sikdar, Sujit Kumar
Abstract : Key points: The physiological metabolite, lactate and the two‐pore domain leak potassium channel, TREK1 are known neuroprotectants against cerebral ischaemia. However, it is not known whether lactate interacts with TREK1 channel to provide neuroprotection. In this study we show that lactate increases TREK1 channel activity and hyperpolarizes CA1 stratum radiatum astrocytes in hippocampal slices. Lactate increases open probability and decreases longer close time of the human (h)TREK1 channel in a concentration dependent manner. Lactate interacts with histidine 328 (H328) in the carboxy terminal domain of hTREK1 channel to decrease its dwell time in the longer closed state. This interaction was dependent on the charge on H328. Lactate‐insensitive mutant H328A hTREK1 showed pH sensitivity similar to wild‐type hTREK1, indicating that the effect of lactate on hTREK1 is independent of pH change. Abstract: A rise in lactate concentration and the leak potassium channel TREK1 have been independently associated with cerebral ischaemia. Recent literature suggests lactate to be neuroprotective and TREK1 knockout mice show an increased sensitivity to brain and spinal cord ischaemia; however, the connecting link between the two is missing. Therefore we hypothesized that lactate might interact with TREK1 channels. In the present study, we show that lactate at ischaemic concentrations (15–30 mm ) at pH 7.4 increases TREK1 current in CA1 stratum radiatum astrocytes and causes membrane hyperpolarization. We confirm the intracellular action of lactate on TREK1 in hippocampal slices using monocarboxylate transporter blockers and at single channel level in cell‐free inside‐out membrane patches. The intracellular effect of lactate on TREK1 is specific since other monocarboxylates such as pyruvate and acetate at pH 7.4 failed to increase TREK1 current. Deletion and point mutation experiments suggest that lactate decreases the longer close dwell time incrementally with increase in lactate concentration by interacting with the histidine residue at position 328 (H328) in the carboxy terminal domain of the TREK1 channel. The interaction of lactate with H328 is dependent on the charge on the histidine residue since isosteric mutation of H328 to glutamine did not show an increase in TREK1 channel activity with lactate. This is the first demonstration of a direct effect of lactate on ion channel activity. The action of lactate on the TREK1 channel signifies a separate neuroprotective mechanism in ischaemia since it was found to be independent of the effect of acidic pH on channel activity. Key points: The physiological metabolite, lactate and the two‐pore domain leak potassium channel, TREK1 are known neuroprotectants against cerebral ischaemia. However, it is not known whether lactate interacts with TREK1 channel to provide neuroprotection. In this study we show that lactate increases TREK1 channel activity and hyperpolarizes CA1 stratum radiatum astrocytes in hippocampal slices. Lactate increases open probability and decreases longer close time of the human (h)TREK1 channel in a concentration dependent manner. Lactate interacts with histidine 328 (H328) in the carboxy terminal domain of hTREK1 channel to decrease its dwell time in the longer closed state. This interaction was dependent on the charge on H328. Lactate‐insensitive mutant H328A hTREK1 showed pH sensitivity similar to wild‐type hTREK1, indicating that the effect of lactate on hTREK1 is independent of pH change.